An Analysis of the use of Tiocetam in Hepatic Encephalopathy - Shmanko, Oleh (Asian Journal of Pharmaceutics (AJP), 2019)
Aim and Scope: Hepatic encephalopathy in liver cirrhosis affects up to 40% of patients. It is important that the hepatic encephalopathy has a potentially reversible nature on the initial stages and is irreversible on the final stages. Therefore, the application of an effective treatment is important for the prognosis of the disease. In the treatment of hepatic encephalopathy, it is important to have a protein restriction diet and drugs that reduce the level of ammonia in the body. Along with this, there is still an insufficiently studied influence of hepatic encephalopathy medications with cerebroprotective capabilities on the clinical symptoms. Taking into account, the multifactorial effects of piracetam and thiotriazoline on metabolic and bioenergetic mechanisms in the body, a combined drug was developed – tiocetam, which consists of 0.2 g of piracetam and 0.05 g of thiotriazoline. In recent years, clinical trials have been conducted on the effectiveness of the use of tiocetam in neurology, which have shown its positive effects on the functional state of the central nervous system, and taking into account, the known hepatoprotective properties of thiotriazoline, it makes sense to study its possible effectiveness in the treatment of hepatic encephalopathy. Therefore, the purpose of our work was to study the effectiveness of tiocetam in patients with hepatic encephalopathy due to liver cirrhosis. Materials and Methods: For the study, 62 patients with liver cirrhosis, Class B (Child–Pugh score) with the signs of hepatic encephalopathy of Grades I and II, were selected. All of them underwent 2 weeks of common treatment, which included milk thistle, S-adenosylmethionine, diuretics, enzyme replacement therapy, and systemic enzyme therapy. All patients were divided into two groups, randomized by age, sex, and severity of manifestations of liver cirrhosis and hepatic encephalopathy: The comparison group – 20 patients, who continued the above course of common treatment; the main group – 42 patients, who were additionally prescribed tiocetamin 2 tablets 3 times/day for 1 month. The control group consisted of 20 healthy individuals. To assess treatment results, the dynamics of clinical manifestations of liver cirrhosis was studied. The degree of sleep disturbance was expressed in points: Mild – 1 point, moderate – 2 points, and severe (lethargy) – 3 points. The state of cognitive function was evaluated using the 10 words memory test; the severity of depression was evaluated applying Hamilton Depression Scale and Beck Depression Inventory. Results and Discussion: An assessment of the general condition of patients 1 month after the beginning of the study revealed a positive dynamics of clinical symptoms in 90.5% of patients in the main group and in 65.0% of patients in the comparison group; furthermore, there was a marked improvement of several biochemical parameters in both treatment groups relative to the control group and to the levels before treatment. There was also an improvement in the quality of sleep, the state of cognitive function, and the severity of depression in the main group relative to the comparison group and to the levels before treatment. Conclusion: The analysis of the results of the use of a combined drug – tiocetam, which consists of 0.2 g of piracetam and 0.05 g of thiotriazoline, in the treatment of hepatic encephalopathy of Grades I and II in patients with subcompensated liver cirrhosis, showed significant clinical effect, namely: Reliable improvement of general condition, several key biochemical parameters, sleep disturbances, cognitive function, and also resulted in a reduction of manifestations of depression, all of which improved the quality of life of patients.